Outstanding optical temperature sensitivity and dual‐mode temperature‐dependent photoluminescence in Ho3+‐doped (K, Na)NbO3–SrTiO3 transparent ceramics. Issue 8 (13th February 2019) - Lin, Jinfeng; Lu, Qiling; Xu, Jie; Wu, Xiao; Lin, Cong; Lin, Tengfei; Chen, Chao; Luo, Laihui
Abstract: High optical temperature sensing properties based on rare‐earth‐doped (K, Na)NbO3 ‐based ferro‐/piezoelectrics have attracted much attention due to their potential application in novel optoelectronic devices. Here, we fabricated Ho 3+ ‐doped (K0.5 Na0.5 )NbO3 –SrTiO3 transparent ceramics by conventional pressureless sintering. Their microstructures, transmittances, up‐conversion photoluminescence, and optical temperature sensing properties have been characterized in details. Because of the cubic‐like phase, dense, and fine‐grained structure as well as relaxor‐like feature, the ceramics exhibit high transmittance (~70%) in the near‐infrared region. Owing to Ho 3+, green and red up‐conversion emissions have been observed, which can be easily modulated by temperature. The ceramics have stable emission colors (<200°C) and superior temperature‐modulating emission color‐tunable performance (>200°C). Furthermore, the temperature sensing behavior based on the thermally coupled levels ( 5 F4, 5 S2 ) of Ho 3+ has been analyzed by a fluorescence intensity ratio technique. The transparent ceramics possess outstanding optical temperature sensitivity (~0.0096/K at 550 K), higher than most rare‐earth‐doped materials (e.g., ceramics, glasses, and phosphors).